Analisis Pengendalian Risiko Korosi pada Material yang Disebabkan oleh Kelebihan Persediaan Menggunakan Metode Kanban Reduction - Dony Bayu Leksono; Melco Wanjaya; Monika Lestari; Niki Farras Al Ghalidza Vannie; Yudi Prastyo (Journal of Science, Technology, and Innovation, 2025)
manufacturing systems. This condition causes materials to experience longer storage times, thereby increasing the risk of physical damage, especially corrosion of metal materials. This study aims to analyze the factors causing corrosion risks triggered by overstocking, and evaluate the implementation of Kanban Reduction as an inventory control strategy to reduce material exposure to corrosive environments. The methods used include field observation, measuring warehouse humidity levels, analyzing inventory before and after Kanban Reduction, and recalculating the number of kanban cards. The results show a decrease in WIP levels by 35.4%, a reduction in storage time from 14 to 6 days, and a decrease in scrap due to corrosion from 10.8% to 3.2%. These findings reinforce that Kanban Reduction is not only relevant for production flow efficiency but also for mitigating corrosion risks in materials. This study analyzes stock records using tools such as Fishbone diagrams and the 5S method. The study results showed that stock discrepancies were caused by incomplete in/out transactions, defective goods undergoing remelting, and unrecorded goods. Proposed improvements include implementing the 5S method to improve warehouse organization and stricter stock recording controls.